EFEKTIVITAS PEMUSATAN LATIHAN ATLIT DI PROVINSI RIAU - Raufanto, Younggi; Sahuri, Chalid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Younggi Raufanto. 1101111462. Effectivity Excercise Centeringâ€™s Athlete in Riau Province. Guidanced by Chalid SahuriBased excercise centeringâ€™s athlete in Riau Province, since two last year gotting data that excercise centeringâ€™s athlete increasing every single year. But the problem is not yet achieve maximum and occuring different achievement result on every sport chapter. Problem formulation on this research is â€œEffectivity excercise centeringâ€™s athlete in Riau Province and factor that influencing effectivity of excercise centeringâ€™s athlete in Riau Province with purpose to knowing effectivity centeringâ€™s athlete in Riau Province and knowing factor that influencing the effectivity of excercise centeringâ€™s athlete in Riau Province.This research uses qualitative descriptive method that explains a thing based on reality found in the field about effectivity excercise centeringâ€™s athlete the data that we use on this research consist of (organization character, area character, worker character, policy and management practice) and secondary ( history, organization structure, resaurces, visi and misi, duty and main function). Technique of data collecting include : observation, interview, study library. Involving the head master of Dispora Riau Province.Result of this research is effectivity of excercise centeringâ€™s athlete in Riau Province is going enough effectively and agree with the target that Dispora wont to reach with applying organization character, area character, worker character, policy and management practice. The successing of excercise centeringâ€™s athlete is â€œenough successâ€ because not at all factors effective on this thing is gotting athleteâ€™s achievement in Riau Province with appying affectivity concept centering with orientation UU number 3 year 2005 about sport system.Key words : Efectivity, excercise centeringâ€™s athlete.